CULTIVATING GLOBAL CITIZENS: ISLAMIC HIGHER EDUCATION"™S ROLE IN FOSTERING INTERCULTURAL COMMUNICATION SKILLS - Asmira, Mita; Indrawati, Johara (Jurnal Visi Ilmu Pendidikan, 2024)
This research addresses the gap in the exploration of intercultural communication skills within Islamic higher education, focusing on Universitas Islam Internasional Darullughah Wadda"™wah. The study aims to unravel the nuanced landscape of global citizenship cultivation in this specific context, emphasizing the distinct features of Islamic higher education. Employing a survey design, data was gathered from 25 undergraduate students, revealing insights into their perceptions and applications of intercultural communication skills. The findings indicate a high level of awareness among students of cultural nuances, with a simultaneous recognition of challenges in practical application. While students demonstrate a positive orientation towards adaptability and cultural sensitivity, the study highlights areas for targeted interventions, particularly in translating theoretical knowledge into practical scenarios. The implications of this research extend to the refinement of educational practices within Islamic higher education institutions, emphasizing the importance of aligning theoretical understanding with practical application for effective global citizenship cultivation